A H+-ATPase That Energizes Nutrient Uptake during Mycorrhizal Symbioses in Rice and Medicago truncatula . Issue 4 (29th April 2014) - Wang, Ertao; Yu, Nan; Bano, S. Asma; Liu, Chengwu; Miller, Anthony J.; Cousins, Donna; Zhang, Xiaowei; Ratet, Pascal; Tadege, Million; Mysore, Kirankumar S.; Downie, J. Allan; Murray, Jeremy D.; et al.
Abstract : Electrochemical H + gradients are essential to drive active transport of solutes through plant membranes. This work describes plant mutants defective in a proton pump that is specifically located in arbuscule-containing root cells and shows that this proton pump is required for the function of the arbuscular mycorrhizal symbiosis and symbiosis-driven phosphate acquisition and plant growth. Abstract: Most plant species form symbioses with arbuscular mycorrhizal (AM ) fungi, which facilitate the uptake of mineral nutrients such as phosphate from the soil. Several transporters, particularly proton-coupled phosphate transporters, have been identified on both the plant and fungal membranes and contribute to delivering phosphate from fungi to plants. The mechanism of nutrient exchange has been studied in plants during mycorrhizal colonization, but the source of the electrochemical proton gradient that drives nutrient exchange is not known. Here, we show that plasma membrane H + -ATPases that are specifically induced in arbuscule-containing cells are required for enhanced proton pumping activity in membrane vesicles from AM -colonized roots of rice ( Oryza sativa ) and Medicago truncatula . Mutation of the H + -ATPases reduced arbuscule size and impaired nutrient uptake by the host plant through the mycorrhizal symbiosis. Overexpression of the H + -ATPase Os-HA1 increased both phosphate uptake and the plasma membrane potential, suggesting that this H + -ATPase plays a key role in energizing the periarbuscular membrane, thereby facilitating nutrient exchange in arbusculated plant cells.